Laminin γ1 chain is essential for the cardiorespiratory and muscular systems - Gawlik, Kinga I.; Bölükbas, Deniz A.; Daoud, Fatima; Peruzzi, Niccolò ; 0000-0002-2929-4247; Welinder, Ellinor; Wendt, Trevor S.; Martinez, Marycarmen Arévalo; Tas, Sinem; Holmberg, Johan; Gvazava, Nika; Ansar, Saema; Albinsson, Sebastian; et al. (Matrix Biology, 2025)
Laminins are basement membrane components that regulate a plethora of biological processes. Despite decades of research, the exact roles of laminins in different tissues and in organogenesis remain to be elucidated. Here, we investigated the function of laminin γ1 chain in heart, lung and other tissues by generating a mouse that lacks laminin γ1 in cells expressing SM22α (Tagln) (LMγ1 flox/SM22α Cre mouse, referred to as LMγ1KO). Laminin γ1 deletion led to basement membrane disruption around cardiomyocytes, smooth muscle cells, alveolar cells and skeletal muscle. This, in turn, led to perinatal death of conditional LMγ1KO mice. Synchrotron-based imaging revealed developmental heart abnormalities: ventricular and atrioventricular septal defects. Lung tissue from embryos and newborns showed impaired alveolization and this defect was not reversed ex vivo. We also created adult inducible laminin γ1 knockout mice (iLMγ1KO) with targeted knockdown in all tissues, and they exhibited decreased contractility of smooth muscle in colonic and arterial tissue. Finally, both LMγ1KO neonates and iLMγ1KO adults displayed severe dystrophic features in skeletal muscle. In summary, our study reveals novel roles for laminin γ1 chain and basement membranes in heart, lung, skeletal and smooth muscle. Compromising basement membranes around various cell types expressing SM22α during embryonic development did not impair early organogenesis of lung, heart and skeletal muscle, but rather disturbed late developmental events in these tissues. Our results could help to understand clinical implications for patients with laminin α2 chain mutations (muscular dystrophy) and laminin α4 mutations (cardiomyopathy), but also for patients with congenital heart disease and lung diseases.
Keywords: Basement membrane; Cardiomyocyte; Collagen IV; Congenital heart disease; Laminin; Lung development; Smooth muscle cell